Meeting international self-report muscle strengthening guidelines is associated with better cardiovagal baroreflex sensitivity in adults - Waghorn, Jocelyn; Schwartz, Beverly D.; Shivgulam, Madeline E.; Wu, Yanlin; Kimmerly, Derek S.; O’Brien, Myles W. (Frontiers in Sports and Active Living, 2024)
Engaging in muscle strengthening activities (e.g., resistance training) at least twice/week is promoted by (Inter)national movement guidelines. Cardiovagal baroreflex sensitivity (cvBRS) reflects the ability to modulate R-R interval in response to changes in systolic blood pressure.Given the current conflicting literature, this study posed to explore the relationship between selfreport muscle strengthening frequency and spontaneous cvBRS. 114 adults (62 females; age: 33 ± 19 years, 22% > 55 years; body mass index: 24.2 ± 3.7 kg/m 2 ) self-reported their weekly muscle strengthening activity frequencies via the Physical Activity and Sedentary Behaviour Questionnaire. Supine beat-by-beat R-R intervals (electrocardiography; 1.00 ± 0.18s (0.90-1.50s)) and systolic blood pressure (via finger photoplethysmography; 116 ± 11 mmHg (93-151 mmHg)) were recorded for 10.7 ± 2.0 mins (5.3-14.5 mins). Spontaneous cvBRS was assessed using the sequence technique. Data were analyzed using multiple regressions adjusted for age, sex, body mass index. Participants completed 2 ± 2 (0-7) days/week of muscle strengthening activities (56% met guidelines), and average overall cvBRS was 14.9 ± 9.1 (3.1-48.4) ms/mmHg. Higher reported frequencies were positively associated with overall cvBRS (Adjusted R 2 = 0.40, p<0.001; 𝛽 = 2.24, p<0.001). Meeting muscle strengthening activity guidelines was associated with improved overall cvBRS (Adjusted R 2 = 0.29, p<0.001; 𝛽 = 7.68, p<0.001). All results were unchanged if cvBRS for up-sequences or down-sequences only were used (all, p<0.001). In conclusion, engaging in muscle strengthening exercises and particularly meeting existing guidelines were associated with better beat-by-beat vagally-mediated blood pressure regulation.